2008
DOI: 10.1152/jn.01393.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fast Locomotor Burst Generation in Late Stage Embryonic Motility

Abstract: Bradley NS, Ryu YU, Lin J. Fast locomotor burst generation in late stage embryonic motility. J Neurophysiol 99: 1733-1742, 2008. First published February 13, 2008 doi:10.1152/jn.01393.2007. We examined muscle burst patterns and burst frequencies for a distinct form of repetitive leg movement recently identified in chick embryos at embryonic day (E)18 that had not been previously studied. The aim was to determine if burst frequencies during repetitive leg movements were indicative of a rhythm burst generator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 40 publications
5
46
0
Order By: Relevance
“…1A) activates LG proprioceptors, or whether their central synapses are inhibited by other spinal and/or descending pathways. For example, as embryos outgrow egg volume, the shell wall potentially imposes passive mechanical constraints by limiting working ranges for posture and movement (Bradley et al, 2005;Sharp et al, 1999), but it is unclear whether extensive foot contact and limb loading occur during RLMs (Bradley et al, 2008). We have only observed sustained leg-shell contact, accompanied by tonic extensor EMG or extensor-flexor coactivity, during prehatching postural extensions associated with body rotation (N.S.B., unpublished).…”
Section: Role Of Proprioception Prior To Hatchingmentioning
confidence: 85%
See 3 more Smart Citations
“…1A) activates LG proprioceptors, or whether their central synapses are inhibited by other spinal and/or descending pathways. For example, as embryos outgrow egg volume, the shell wall potentially imposes passive mechanical constraints by limiting working ranges for posture and movement (Bradley et al, 2005;Sharp et al, 1999), but it is unclear whether extensive foot contact and limb loading occur during RLMs (Bradley et al, 2008). We have only observed sustained leg-shell contact, accompanied by tonic extensor EMG or extensor-flexor coactivity, during prehatching postural extensions associated with body rotation (N.S.B., unpublished).…”
Section: Role Of Proprioception Prior To Hatchingmentioning
confidence: 85%
“…Under control conditions, TA burst frequency can vary from 1 to 10 Hz without any apparent variation in postural context or modulation in TA burst duration (Bradley et al, 2008). While these features attest to the central generation of RLMs, they also suggest there is no sensorimotorrelated modulation, like that imposed by a changing belt speed during treadmill locomotion, to account for the parameter variations.…”
Section: Role Of Proprioception Prior To Hatchingmentioning
confidence: 90%
See 2 more Smart Citations
“…We studied the hypoxic effect on cyclic motility until D15 inclusive. Then the motility character was beginning to gradually change mainly due to the appearance of repetitive limb movements that have been described by Bradley et al [23], and the cyclic character of the motility became less pronounced. Other authors have also reported an increased variation of the parameters of cyclic motility (APh and IPh) with embryonic age [16,24,25].…”
Section: Age-related Changes In Cyclic Motility Under Normoxic Conditmentioning
confidence: 88%